Upaya Peneguhan Eksistensi Lembaga Amil Zakat Sebagai Salah Satu Bentuk Faith Based Organization di Indonesia - Sari Viciawati Machdum (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2013)
Zakah in Indonesia has a great potential in contributing the improvement of life quality of people in need in Indonesia. With this such potential, many Amil Zakah Institutions (Lembaga Amil Zakat/LAZ) are founded in Indonesia as faith based organizations (FBO). The literatures mentioned that Faith Based Organization has already taken its own place in the world of Social Work and Social Welfare. This article discussed the LAZ existence as one of the FBO in Indonesia. Utilization of zakah from charity to empowerment--including economic empowerment—has been an evidence that LAZ evolved into a better direction. This certainly can negate the negative stigma that has been pinned to social services of the FBO. Keywords: faith based organization, human service organization, manajemen, lembaga amil zakat